PENGEMBANGAN PROTOTYPE ALAT BANTU PEMBELAJARAN MENULIS BAHASA INDONESIA BERDASARKAN PENERAPAN TEORI OTOMATISASI DENGAN PENGUJIAN TAM - Jantika Chandra (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Learning Indonesian language is an important part of education. To support students learning Indonesian languange made to learn in a way that is interesting and theory automation can remember what is learned. This study aims to develop and test a prototype tool of learning to write. Critical theory is a theory automation and technology acceptance models. The results of this research is the development of a prototype in which there are learning content and practice. The results obtained in this study are: (a) Prototype learning writing tool can help students in learning Indonesian writing, (b) students receive a well where the prototype, and (c) Assessment of the effect between the variables of perceived ease of use, perceived usefulness and behavioral intention to find out the desire of the students in using the prototype tool of learning to write. Key words Bahasa Indonesia, prototype, technology acceptance model, teori otomatisasi